A Rare Case of Xanthogranulomatous Osteomyelitis of Radius Presenting as Pathological Fracture – A Case Report - Syam Gangadharan Nair; Jittu Alex; Riyas Nazar; John Thayyil John (Journal of Orthopaedic Case Reports)
Introduction: Xanthogranulomatous inflammation is a specific form of chronic inflammatory disease histologically characterized by collection of foamy macrophages along with polymorphonuclear leukocytes, activated plasma cells, and lymphocytes of polyclonal origin, in a mosaic-like pattern. The involvement of xanthogranulomatous inflammation of the bone is termed as xanthogranulomatous osteomyelitis (XO). It often presents as a mass-like lesion extending into adjacent structures and so radiological features have little role in pointing to a diagnosis. Definitive diagnosis can only be made by histopathological examination. Case Report: This report describes a case of 62-year-old male patient who sustained a pathological fracture of shaft of radius which on evaluation, was diagnosed as XO, its management and 2- year follow-up results. This case report highlights a rare cause of pathological fracture, that is, XO. Conclusion: Clinical examination and radiology have little role in the diagnosis of the condition. Definitive diagnosis is achieved by histopathological examination and the disease has a good prognosis.